“Já experimentou para saber se gosta?” – assexualidades na sociedade sexualizada - Neiva, Giórgia de Aquino (2019)
This thesis reflects anthropologically on relations between identity, political movement and the discursive production of categories and conventions around asexualities - a term broadly mobilized to name the sexual orientation of people who have no interest in sex. The empirical material was produced from field work carried out in the period from 2015 to 2017 and took into account that the internet plays a prominent role in the theoretical production and political performance of subjects who are recognized as asexual in contemporary times. Thus, he included participant observation in an online forum called the Assexual Community (A2) and a group of a cross- platform application of instant messaging and voice calls to smartphones, both made up of people who recognize themselves as asexual. In addition, it included observations and dialogues established in face-to-face meetings and semi-structured interviews with some of these people, as well as the application of an online questionnaire. In the paper, I present and discuss the ways in which asexualities are discursively produced from biomedical knowledges that universalize, naturalize and pathologize certain dynamics around sexuality, anchored in heteronormative expectations, moral conventions and biological and physiologicalist assumptions. Thus, I contextualize critically asexualities in biomedical and psychiatric discourses based on diagnostic and statistical manuals of mental illness. Based on the material produced through the field work, I interpret possible effects of the struggle for political visibility of and in asexualities and the search for its despatologization, which aims to make them less loaded with prejudices and stigmata. Finally, I analyze dynamics related to tastes and lifestyles around asexualities, to corroborate with the notion that there are multiple understandings on the subject between subjects who are recognized as asexual, including the narratives that approach asexualities of the notion of sexual orientation. It is concluded in this thesis that the asexualities are inserted in the historical device of the sexuality, since also it is (re) produces, from them and on them, certain discursive regimes presumed true on the sex. Finally, I wonder if the production of other knowledges about asexualities, many of them (re)produced by asexual people, have the potential to call into question canonical theories of the so called western societies and if they bring possibilities to deconstruct prejudices and stigmas about expressions of sexuality culturally dissidents.